Effects of Frequent Announced Parasitology Quizzes on the Academic Achievement - Ghasem Zamini; Mohammad Bagher Khadem Erfan; Mohammad Reza Rahmani; Mohammad Sadegh Khodavaisy; Behroz Davari (Iranian Journal of Parasitology, 2013)
Background: The effect of frequent examinations on the students’ learning has had inconsistent results. This study aimed to assess the effectiveness of fre-quent announced quizzes on the learning of a representative sample of Iranian medical students.